Cyproterone Acetate Quantification in Human Plasma by High-performance Liquid Chromatography Coupled to Atmospheric Pressure Photoionization Tandem Mass Spectrometry - Borges, Ney Carter; Mazuqueli, Ana; Moreno, Ronilson Agnaldo; Astigarraga, Rafael Barrientos; Sverdloff, Carlos Eduardo; Galvinas, Paulo Alexandre Rebelo; Sampaio, Mauício Rocha de Magalhães; Silva, Washington Moreira da (Arzneimittelforschung, 2009)
A specific, fast and sensitive high performance liquid chromatography (HPLC) coupled to atmospheric pressure photoionization (APPI) tandem mass spectrometric (LC-MS/MS) assay was developed for the determination of cyproterone (CYP) acetate (CAS 427-51-0) in human plasma. The retention times were 3.26 and 2.90 min for CYP acetate and its internal standard (I. S.) finasteride (FIN), respectively. The overall mean recovery, using liquid/liquid extraction, was found to be 109.0, 107.7 and 100.3%, for low, medium and high concentrations, respectively. Calibration curves were linear in the concentration range of 0.1–50.0 ng/ml, and the lower limit of quantification (LLOQ) was 0.1 ng/ml. The LLOQ, 0.1 ng/ml, was sensitive enough for detecting terminal phase concentrations of the drug. Inter-batch precision of the method ranged from 2.2 to 5.55%, while Inter-batch accuracy ranged from 95.5 to 100.0%. Intra-batch precision ranged from 1.8 to 5.6%, while Intra-batch accuracy ranged from 92.0 to 99.4% at concentrations of 0.3 ng/ml, 20.0 and 40.0 ng/ml. The developed method was applied to a bioequivalenc study of CYP acetate in a group of 44 female volunteers at a single oral dose of a 2 mg tablet, in a combination of ethinylestradiol/CYP acetate (0.25/2 mg). The plasma concentration of CYP acetate did not differ significantly after administration of both formulations (test formulation and the reference one). The geometric mean and respective 90% CI of CYP acetate test/reference percent ratios were 90.66% (84.39–97.40%) for Cmax and 96.20% (90.45-102.33%) for AUC0–t.
Keywords: Antiandrogenic drugs; CAS 427-51-0; Cyproterone acetate, bio-equivalence, liquid chromatography; tandem mass spectrometry, pharmacokinetics; Progestogenic drugs